Farm Efficiency Evaluation through FADN Database - Furesi R.; Nencioni C.M.; Pulina P.; Rubino R. (Systems of sheep and goat production: Organization of husbandry and role of extension services, 1999)
The aim of the work is to identify the most important factors which distinguish the different ewes and goat milk production systems found in Italy. Basic quantitative information for the analysis comes from specialized farms belonging to the Italian Farm Accounting Data Network (FADN) sample. By using multivariate statistical tools the most important economic and technical parameters defining the differences between the observed production systems are individualized and evaluated. The comparison between analysis results and production system performances allows us to identify possible constraints and/or successful conditions. Such information can be of use when orienting sectorial and local development strategies and policies.
Symposium of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 25-27 Oct 1997, Bella (Italy)